X–ray analysis of irradiated nuclear graphite of grades ARV and MPG - Комир, Антон Игоревич; Одейчук, Николай Петрович; Николаенко, Алиса Александровна (Eastern-European Journal of Enterprise Technologies, 2015)
In connection with the research of structural materials for Generation IV nuclear energy systems, there is interest in increasing the accuracy of simulating the hypothetical accidents such as atmosphere entry into the core. To substantiate the possibility of using the concept of oxidation simulation by the finite element method with isotopic properties, a study of the anisotropy of the crystal structure of nuclear graphite produced by isostatic compression is needed. X-ray analysis of nuclear-grade graphite ARV and MGP in the initial and the irradiated state is performed in the paper. Three different phases of graphite due to the method of production were identified. The influence of gamma radiation and streams of high-energy electrons on the crystal structure was examined. The issue of еру anisotropy of еру crystal structure and its change under ionizing radiation was investigated. The hypotheses of a slight anisotropy of the crystal structure of the studied graphite grades were confirmed.